TRANSFORMASI DIGITAL PERBANKAN DAN URGENSI PERLINDUNGAN HUKUM NASABAH TERHADAP ANCAMAN KEJAHATAN SIBER DI INDONESIA - Robert L Simanungkalit; Ruby W H Oktolina Samosir (Pojok Publisher, 2026)
The rapid development of information technology has shifted the banking paradigm from conventional banking to a digital ecosystem (Industry 4.0 and 5.0). While offering efficiency and financial inclusion through services such as Mobile Banking, QRIS, and e-Wallets, this digitalization brings new risks in the form of cybercrime and misuse of personal data. This article aims to analyze the legal protection framework for bank customers in Indonesia in the context of digital transactions. Using normative research methods, this study examines the relationship between the Banking Law, the ITE Law, and the Personal Data Protection Law (PDP Law). The discussion shows that legal protection for customers must be based on the principles of justice, transparency, and security. Synergy is needed between regulatory authorities (OJK and BI) and increasing public digital literacy and strengthening banking technology security systems to mitigate the risks of cybercrime and Money Laundering (TPPU).